Epidural Steroid Injections are Safe and Effective: Multisociety Letter in Support of the Safety and Effectiveness of Epidural Steroid Injections. Issue 5 (13th January 2015) - Kennedy, David J.; Levin, Joshua; Rosenquist, Richard; Singh, Virtaj; Smith, Clark; Stojanovic, Milan P.; Vorobeychik, Yakov
Abstract Background: In April 2014, the Food and Drug Administration (FDA) issued a Drug Safety Communication requesting that corticosteroid labeling include warnings that injection of corticosteroids into the epidural space of the spine may result in rare but serious adverse events, including loss of vision, stroke, paralysis, and death. Results: The International Spine Intervention Society spearheaded a collaboration of more than a dozen other medical societies in submitting the letter below to the FDA on November 7, 2014. We are publishing the letter to ensure that the readership of Pain Medicine is aware of the multisociety support for the safety and effectiveness of these procedures. A special note of thanks to all of the societies who signed on in support of the message.